Control of electric machine drive system - Sul, Seung-Ki (IEEE Press series on power engineering ;, 2011)
"This book is based on the author's industry experience. It contains many exercise problems that engineers would experience in their day-to-day work. The book was published in Korean at 500 pages as a textbook. The book will contain over 300 figures. The author plans to have an FTP site to provide some MATLAB programs for selected problems"--